2017
DOI: 10.1089/ars.2016.6735
|View full text |Cite
|
Sign up to set email alerts
|

The Heme Oxygenase System in Hematological Malignancies

Abstract: The HO system may serve as an important tool in the field of hematological malignancies because it can be exploited to counteract chemoresistance and to monitor the outcome of bone marrow transplants and may be an additional target for combined therapies. Antioxid. Redox Signal. 27, 363-377.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 112 publications
1
29
0
1
Order By: Relevance
“…In agreement with previous results, showing the ability of carnosine to indirectly counteract oxidative stress by enhancing the expression of members of the endogenous antioxidant system, including HO-1 and Nrf2 [56][57][58], under our experimental conditions we found that carnosine up-regulated both Nrf2 and, particularly, its downstream product HO-1 (Figure 8). Since the activity of HO-1 has been addressed as one of the main actors in the defense system towards oxidative/nitrosative stress [10,[59][60][61][62], it is presumable that the carnosine-mediated positive HO-1 modulation contributes in part to the generalized decrease in metabolic indicators of sustained oxidative/nitrosative stress (sum of nitrite + nitrate, MDA; Figures 2 and 6). On the other hand, carnosine effects on Nrf2 might have led stimulated macrophages to have lower expressions of Nox-2 and Cox-2 and concomitant higher expressions in canonical scavenger enzymes (Gpx, Cat, and SOD-2; Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with previous results, showing the ability of carnosine to indirectly counteract oxidative stress by enhancing the expression of members of the endogenous antioxidant system, including HO-1 and Nrf2 [56][57][58], under our experimental conditions we found that carnosine up-regulated both Nrf2 and, particularly, its downstream product HO-1 (Figure 8). Since the activity of HO-1 has been addressed as one of the main actors in the defense system towards oxidative/nitrosative stress [10,[59][60][61][62], it is presumable that the carnosine-mediated positive HO-1 modulation contributes in part to the generalized decrease in metabolic indicators of sustained oxidative/nitrosative stress (sum of nitrite + nitrate, MDA; Figures 2 and 6). On the other hand, carnosine effects on Nrf2 might have led stimulated macrophages to have lower expressions of Nox-2 and Cox-2 and concomitant higher expressions in canonical scavenger enzymes (Gpx, Cat, and SOD-2; Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…Under oxidative stress, HO-1 expression is induced by the NRF2 transcription factor as part of the cellular antioxidant defence response. HO-1 is upregulated in some leukaemic cells [ 190 ], which could be a compensatory mechanism to cope with oxidative stress [ 95 ]. It is noteworthy that HO-1 overexpression has been related to drug resistance [ 191 ].…”
Section: The Use Of Ros As a Therapeutic Target In Haematological Malmentioning
confidence: 99%
“…In these cases, HO-1 acts as survival molecule and its up-regulation protects cells from apoptosis, induces cell proliferation, metastasis, angiogenesis by promoting vascular endothelial growth factor (VEGF) expression, and resistance to therapy [71]. Numerous papers describe the involvement of HO-1 in the progression of blood malignancies and in the mechanisms leading to chemo-resistance in leukemia, but also in the progression of solid tumors, such as human renal cell carcinoma, melanoma, and prostate-and pancreatic cancer [72]. Particularly, different studies show that HO-1 is expressed in cytoplasm and also in nucleus of cancer cells in lung, prostate and oral tumor tissues.…”
Section: Hemeoxygenase-1 Induction In Cancer Progressionmentioning
confidence: 99%